G234(P) An audit on the assessment and management of paediatric head injuries. (27th April 2016) - Khan, M; Mohammad, M; Hadi, K; Ahmad, S; Hulikere, S
Abstract : Background: Approximately 700, 000 people attend the emergency department (ED) with head injuries in England and Wales of which, paediatric cases make up a high proportion of head injuries presenting acutely. As head injury is a leading cause of disability, the NICE has set guidelines on the initial assessment and management of head injuries in order to achieve the best patient outcomes. Aims: To identify the assessment and management methods applied to paediatric patients presenting with head injuries at our ED and compare findings with current NICE guidelines in order to highlight areas requiring improvement. Methods: Data was collected on patients aged 0–17 years old presenting with a head injury at our ED. Clinical notes were used to assess the level of assessment and management and compared with current NICE guidelines. Results: 462 patients (median age of 3) were included. 98% (n = 453) presented with a clear mechanism of injury. Headaches were documented in 43% (n = 236). Other signs and symptoms included vomiting (15%), altered behaviour (12.5%), seizures (2%) and loss of consciousness (5%). The Glasgow Coma Scale (GCS) was recorded in only 31% (n = 141). Details of any injuries sustained were documented in 89% (n = 410) while signs of basilar skull fractures were only recorded in 33% (n = 152). A neurological exam was documented in 58% (n = 267) of cases. CT scan was indicated in only 8 patients with 4 being performed and reported within 1 h of presentation. 96% (n = 444) were discharged on the same day with 99% (n = 440) receiving written and verbal head injury advice. Conclusion: There was a lack of thorough history taking relevant to head injuries and the GCS and examination findings were inadequately documented. Only half of CT scans were taken and reported within the recommended NICE time frame. To improve the care of paediatric head injuries, we suggest that the GCS can be potentially assessed during the initial nurse-led assessment of the patient and have formulated an ED head injury performa to standardise the initial assessment and management of paediatric head injuries.